2002
DOI: 10.1038/sj.bjp.0704755
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of nitric oxide in articular inflammatory pain in zymosan‐induced arthritis in rats

Abstract: The contribution of nitric oxide (NO) to articular pain in arthritis induced by zymosan (1 mg, intra articular) in rats was assessed by measuring articular incapacitation (AI). Systemic treatment with the non‐selective NO synthase (NOS) inhibitor L‐NAME (10–100 mg kg−1 i.p.) or with the selective iNOS inhibitors aminoguanidine (AG; 10–100 mg kg−1 i.p.) or 1400W (0.5–1 mg kg−1 s.c.) inhibited the AI induced by injection of zymosan 30 min later. Local (intra articular) treatment with the NOS inhibitors (L‐NAME o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 48 publications
2
32
0
4
Order By: Relevance
“…A reduction in infl ammatory infi ltrate, associated with reduced L-selectin expression, was described as a consequence of L-NAME treatment in a model of B. jararaca venom-induced infl ammation in rats [46]. Hence, despite confl icting fi ndings on the role of NO in infl ammatory phenomena (see for example [47] and [48]), which may depend on the use of different NOS inhibition protocols and differences in the microvasculature of various tissues, our fi ndings and those of others suggest that NO promotes various aspects of infl ammation in models involving Bothrops sp venom injection. The lack of effect of NOS inhibition in the infl ammatory infi ltrate at 24 and 48 h suggests that infl ammatory mediators other than NO play a predominant role in leucocyte recruitment at these earlier time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in infl ammatory infi ltrate, associated with reduced L-selectin expression, was described as a consequence of L-NAME treatment in a model of B. jararaca venom-induced infl ammation in rats [46]. Hence, despite confl icting fi ndings on the role of NO in infl ammatory phenomena (see for example [47] and [48]), which may depend on the use of different NOS inhibition protocols and differences in the microvasculature of various tissues, our fi ndings and those of others suggest that NO promotes various aspects of infl ammation in models involving Bothrops sp venom injection. The lack of effect of NOS inhibition in the infl ammatory infi ltrate at 24 and 48 h suggests that infl ammatory mediators other than NO play a predominant role in leucocyte recruitment at these earlier time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical hyperalgesia in zymosan-induced arthritis in rats was reduced by local (intraarticular) pretreatment with nonselective or iNOS-selective inhibitors before zymosan injection; however, these drugs were without effect if they were given after development of arthritis (609). As NO donors given locally after development of arthritis inhibited mechanical hyperalgesia without affecting edema, pointing to an antinociceptive effect of NO, the authors ascribed the former effect to inhibition of synovial inflammation by reduced formation of the proinflammatory NO.…”
Section: Opposing Effects Of Nitric Oxide Revealed By Variation Of Exmentioning
confidence: 99%
“…Furthermore, Kim et al reported that SNP in low concentrations protects chondrocytes from toxic effect of the higher concentration [39]. Consistent with the notion of a dual effects of NO donors, several experiments have shown that local application of drugs generating a low NO concentration reduces incision pain through activation of guanylate cyclase while drugs generating high NO concentration intensify pain via guanylate cyclase-independent mechanism [47,48]. With respect to joint pain there is only one clinical study showing that transdermal nitroglycerin provided partial symptomatic pain relief in patient with painful shoulders [49].…”
Section: Discussionmentioning
confidence: 79%